BAGI HASIL PERTANIAN SEMANGKA DALAM PRESPEKTIF EKONOMI ISLAM ( Studi Kasus Di Desa Talang Bukit ) - Defri Amanda; Eja Armaz Hardi; Nurfitri Martaliah (CV. Aksara Global Akademia, 2024)
This research aims to find out the profit sharing in watermelon farming in Talang Bukit village and find out the overview of Islamic economics in watermelon farming practices in Talang Bukit village. This research uses qualitative methods with a field research approach and data collection through observation, interviews and documentation. The results of this research show that the profit sharing system for watermelon farming cooperation in Talang Bukit Village, Kec. North Bahar District. Muaro Jambi is carried out by two parties, namely between the land owner and the cultivator in the form of an oral statement, based on trust and without presenting witnesses with a profit sharing system, namely parohan or pertelon depending on the agreement at the beginning of the contract, and the time period is not clearly specified. In its implementation, the watermelon farming cooperation agreement in Talang Bukit Village, North Bahar District, Muaro Jambi Regency aims to help each other among humans. However, in terms of covering losses, it can be said to be in conflict with the jumhur ulama, because in practice if a loss occurs then only one party will bear it. In this way, one party feels disadvantaged. However, land owners and cultivators are still willing to implement a profit sharing system because this is driven by necessity.